KARAKTER SPASIAL KORIDOR JALAN KAWASAN KAMPUS DALAM KONTEKS URBAN DESIGN DAN PERILAKU: Studi Kasus: Koridor Jalan pada Kawasan Kampus UNSRI Bukit Besar - Fuji Amalia; Sakura Yulia Iryani (Jurnal Koridor, 2018)
UNSRI Bukit Besar has become a core area for decades that have a direct impact on the surrounding area, especially to the city's physical, economic, and social communities. The development and improvement of economic and social have triggered physical changes some urban elements that exist in the road corridor. The influence of this effect has some consequences for conflicts of interest in the use of road space. This research was conducted qualitatively by observing changes due to the existence UNSRI urban elements, which has occurred on the road corridors that restrict direct Campus Region. Mapping had been done to look at the physical condition that occurs when the lecture and after lecture and compare the results with theory and regulations. The results of this study as a reference in the control and development of the area as a result of the existence of Campus of UNSRI Bukit Besar.